2013
DOI: 10.1074/jbc.m113.454892
|View full text |Cite
|
Sign up to set email alerts
|

The Central Nervous System (CNS)-independent Anti-bone-resorptive Activity of Muscle Contraction and the Underlying Molecular and Cellular Signatures

Abstract: Background: Mechanisms by which muscle regulates bone are poorly understood. Results: Electrically stimulated muscle contraction reversed elevations in bone resorption and increased Wnt signaling in bone-derived cells after spinal cord transection. Conclusion: Muscle contraction reduced resorption of unloaded bone independently of the CNS, through mechanical effects and, potentially, nonmechanical signals (e.g. myokines). Significance: The study provides new insights regarding muscle-bone interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 57 publications
2
67
0
Order By: Relevance
“…Second, glucocorticoid excess and vitamin D deficiency are catabolic, whereas androgens are anabolic to both bone and muscle (8,9). Third, we find that, in rats with experimental spinal cord injury, electrical stimulation of muscle rescues the elevated bone resorption and osteoclastogenesis in vivo, in essence providing direct evidence for muscle-bone communication, likely through a soluble molecule (10).…”
mentioning
confidence: 66%
“…Second, glucocorticoid excess and vitamin D deficiency are catabolic, whereas androgens are anabolic to both bone and muscle (8,9). Third, we find that, in rats with experimental spinal cord injury, electrical stimulation of muscle rescues the elevated bone resorption and osteoclastogenesis in vivo, in essence providing direct evidence for muscle-bone communication, likely through a soluble molecule (10).…”
mentioning
confidence: 66%
“…Interestingly, no changes in circulating osteocalcin or C-telopeptide (markers of whole body bone formation and resorption, respectively) were observed after SCI, which is somewhat inconsistent with previous reports indicating increased circulating markers of bone resorption occur in male and female rodents after spinal cord transection. 20,34 These apparent inconsistencies likely result from bone loss and (elevated) bone turnover remaining isolated to bone below the lesion level after SCI (as has been reported in humans) 36 and/or because our model differed in sex (male vs. female), age at time of injury (14 weeks vs. 6-9 weeks), and mode of injury (moderatesevere contusion SCI vs. spinal cord transection) in comparison with previous studies. 20,34 We also observed that animals subjected to SCI exhibited deleterious microstructural alterations in the shape (architecture) of the remaining trabeculae (reported as SMI) indicative of reduced plate-like architecture or increased rod-like trabecular architecture 18 and that high-dose TE prevented these changes.…”
Section: Bone Loss and Bone Turnover After Scimentioning
confidence: 73%
“…20,33,34 This bone loss is characterized by large reductions in cancellous bone mass within the first few years after SCI with cortical bone loss persisting for > 10 years. 3 Similarly, the severe cancellous bone loss that we and others 20,21,35 observed after SCI appears to have resulted from a combination of increased bone resorption, as indicated by an increased osteoclast surface, and reduced bone formation, as indicated by reduced cancellous MAR and BFR/BS.…”
Section: Bone Loss and Bone Turnover After Scimentioning
confidence: 99%
“…Thus, Sost-deficient mice are resistant to bone loss induced by hindlimb suspension, although the contribution of bone formation and/or bone resorption in this model remains unclear [5]. Accordingly, pharmacological inhibition of sclerostin restores bone formation in different models of microgravity, i.e., tail suspension, immobilized rats, and spine injury model [10][11][12][13]. We previously reported that down regulation of SOST and cortical bone formation in response to mechanical loading and parathyroid hormone (PTH) depends on the expression of a matricellular protein, periostin, the expression of which is increased in these conditions [14,15].…”
Section: Introductionmentioning
confidence: 94%